KONSEP DASAR DAN PRINSIP-PRINSIP ASESMEN DALAM PEMBELAJARAN BERBASIS KURIKULUM MERDEKA - Regina Okta Audini; Chintia Essa Bella; Sinta, Adriantoni (STKIP Subang, 2025)
This study examines the fundamental concepts and principles of assessment in learning based on the Merdeka Curriculum, which emphasizes an inclusive, adaptive approach that caters to the diversity of students. In the context of the Merdeka Curriculum, assessment functions not only as a tool for measuring learning outcomes but also as an integral part of the learning process that supports the development of students' competencies and character. The method used is a literature study with a descriptive qualitative approach, reviewing various sources related to assessment, the Merdeka Curriculum policy, and relevant assessment practices. The results of the study indicate that assessments within the Merdeka Curriculum integrate various types of assessments, such as formative, summative, diagnostic, and authentic, aimed at evaluating students' development holistically. The principles of assessment in the Merdeka Curriculum include fairness, diversity, and adaptation to students' characteristics, enabling a more comprehensive evaluation of students' cognitive, affective, and psychomotor abilities. A key challenge identified is the readiness of teachers to implement more diverse and complex assessments, considering the increased administrative burden and insufficient training. The implications of this study highlight the importance of ongoing teacher training to enhance their ability to design and implement assessments that align with the principles of the Merdeka Curriculum.